2022
DOI: 10.1055/a-1744-5868
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Orexin-A into the Rat Thalamic Paraventricular Nucleus Enhances the Naloxone Induced Morphine Withdrawal

Abstract: Objective Orexin neuropeptides are implicated in physical dependence on opioids and expression of withdrawal symptoms in drug abuse. The paraventricular nucleus of the midline thalamus (PVT) has a high expression of orexin receptors. The current research studied the effect of orexin-A in the PVT area on the development of behavioral indices produced by morphine withdrawal in rats. Methods Male Wistar rats weighing 250–300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It has been shown that orexin-A displays analgesic effects analogous to morphine as measured via the hot-plate test. Some evidence displayed that the blockade of OXR1 reduced physical dependence in rats 9 11 . Numerous researches have discovered that orexinergic neurons and receptors are expressed at different levels of the descending pain modulation system 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that orexin-A displays analgesic effects analogous to morphine as measured via the hot-plate test. Some evidence displayed that the blockade of OXR1 reduced physical dependence in rats 9 11 . Numerous researches have discovered that orexinergic neurons and receptors are expressed at different levels of the descending pain modulation system 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%